THE INFLUENCE OF DIGITAL PRINTING TECHNOLOGY AND PRODUCT QUALITY ON THE CREATIVE ECONOMY MEDIATED BY SERVICE QUALITY - Perdana, Ah. Zidny Kafa; Sutinem; Muhtarom, Abid; Yaskun, Mohammad (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Digital printing SMEs are among the key drivers of Indonesia’s creative economy. By producing banners, stickers, t-shirts, and promotional materials, they support other subsectors such as culinary, tourism, and fashion. However, the sustainability of this contribution depends on adopting advanced technology, ensuring consistent product quality, and maintaining service excellence. This study analyzes the influence of digital printing technology and product quality on the creative economy, with service quality as a mediating variable.The model applied is Partial Least Squares Structural Equation Modeling (PLS-SEM). The object of this research is customers of Perdana Digital Printing, Lamongan. The research population consisted of all customers served during April 2025, totaling 260 visitors. Using random sampling, a sample of 150 respondents was selected. Data were collected through a structured questionnaire.The results show that: 1) Digital printing technology significantly improves product quality. 2) Digital printing technology has a positive effect on service quality. 3) Product quality significantly contributes to creative economy outcomes. 4) Service quality positively and significantly influences creative economy outcomes. 5) Service quality partially mediates the relationship between technology and the creative economy. 6) Service quality partially mediates the relationship between product quality and the creative economy